Islam and democracy in the Maldives: interrogating reformist Islam's role in politics - Zahir, Azim (Routledge studies in South Asian politics, 2022)
Introduction -- 1. Interrogating the Reformist Islam Approach -- 2. The Seeding of Islam as a Modern Institutional Political Religion (1932-1978) -- 3. Reformist Islam and Modern Nation Building (1932-1978) -- 4. Islam's emergence as a modern discursive political religion and institutional consolidation (1978-2003) -- 5. Reformist Islam, Human Rights, and Democratisation (2003-2009) -- 6. Explaining Institutionalisation of Islam and Religion-Based Limitations -- Conclusion -- Appendix 1: Key Constitutions Analysed -- Appendix 2: Laws Analysed for Chapter 2 -- Appendix 3: Maldivian Democratic Party (MDP) Newsletters Analysed -- Appendix 4: Constituent Assembly Sessions Analysed -- References -- Index.